2014
DOI: 10.1371/journal.pone.0086143
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cell Carcinogenic Transformation by a Quadruplex DNA Binding Fluorescent Probe

Abstract: Cancer can be easily treated when found early. A probe capable of detecting cell transformation may increase the success rate of early diagnosis of cancer. In this report we have tested the ability of a fluorescent, quadruplex DNA binding probe, 3,6-bis(1-methyl-4- vinylpyridinium) carbazole diiodide (BMVC), to detect cell transformation in vitro. BMVC was applied to living cells in several different models of cell transformation, and the fluorescence signals of BMVC were measured. The degrees of cell transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Early diagnosis of cancer greatly increases the patient's chances of recovery. BMVC was tested in vitro as a probe capable of detecting cell transformation, which may increase such a success [70]. BMVC has been applied to living cells in several different models of cell transformation, and the fluorescence signals of BMVC detecting formation of foci, significantly increased cellular motility, cell proliferation, cell apoptosis, anchorage-independent growth, and increased invasiveness of transformed cells.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Early diagnosis of cancer greatly increases the patient's chances of recovery. BMVC was tested in vitro as a probe capable of detecting cell transformation, which may increase such a success [70]. BMVC has been applied to living cells in several different models of cell transformation, and the fluorescence signals of BMVC detecting formation of foci, significantly increased cellular motility, cell proliferation, cell apoptosis, anchorage-independent growth, and increased invasiveness of transformed cells.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…In 2013, Balasubramanian et al, 8 published one of the first papers that confirmed G4s exist in vivo , which has been further supported by several additional reports on G4s in vivo in both DNA and RNA. 9-13 No similar studies for iMs have been performed, so their existence in vivo is still yet to be determined. Unlike G4s, iMs have not yet been considered widely as stable in vivo since the pH in the nucleus is believed to be not much different than cytosolic pH (~7.3) 14, 15 while the pK a of a typical iM is < 7.0.…”
mentioning
confidence: 99%
“…Considering that the formation of foci in cancer cells in an important feature of carcinogenesis [27], we implemented the clonogenic assay to determine the capacity of CyCl in tumor colony formation. Three colon cancer cells were seeded at very low densities and their capacity to develop colonies was monitored for a period of 2 weeks.…”
Section: Cycl Inhibits Colon Cancer Foci Formationmentioning
confidence: 99%